Índice de briones como predictor de ingreso temprano a UCI en las gestantes con preeclampsia severa y eclampsia en el Hospital Regional de Loreto “Felipe Santiago Arriola Iglesias” durante el periodo mayo 2023 a mayo 2024 - Sattui D´Angelo, Flavio Jesus (2025)
Preeclampsia Preeclampsia is a pregnancy complication characterized by hypertension and the presence of proteins in the urine, affecting several body systems, and can pose serious risks to the mother and fetus if not treated properly. Briones Index In relation to preeclampsia, the Briones index can be useful to evaluate the hydration status and hemodynamic dynamics of the mother. Although the index itself is not a specific marker of preeclampsia, its Analysis can provide information about how fluid retention and electrolyte balance are affected in this situation. Colloidosmotic Pressure Colloidosmotic pressure refers to the pressure exerted by proteins in the plasma, being essential for the balance of fluids between the intravascular and interstitial spaces.